Transforming growth factor β in breast cancer: another new trick for the old dog. Issue 3 (6th December 2020) - Lu, Kun‐Hui; Goel, Shom
Abstract : Two recent papers from the laboratory of Professor Ming Li demonstrate that inhibition of transforming growth factor β specifically in CD4 + T cells can suppress tumor growth through an unanticipated mechanism.